How Chinese fintech threatens US Dollar hegemony - Tharappel, Jayanth (Frontiers in Blockchain, 2023)
This article will argue that the development of Chinese financial technology, or ‘fintech’, over the past decade, is primarily motivated to safeguard Chinese monetary sovereignty, which is threatened by the proliferation of non-state cryptocurrencies, like Bitcoin, that have exacerbated the problem of capital flight, not only for China, but for other non-Western countries that have lost fortunes to outflows seeking access Western financial assets. This raises the question, how is China responding to the emergence of cryptocurrencies as a development that reinforces US financial hegemony? The answer to be explored by this paper is by embracing elements of cryptocurrency technology in the form of digital payment systems and blockchain technology. These Chinese fintech developments pose a serious unprecedented challenge to the financial hegemony of the US insofar as it compels other countries to copy the Chinese response because they desire the tools to limit illegal outflows of capital that have historically propped up the US Dollar.